Hepatitis C virus infection in nephrology patients - Lionel Rostaing; Jacques Izopet; Nassim Kamar (Society of Diabetic Nephropathy Prevention, 2013)
Context: Hepatitis C virus (HCV) infection leads to chronic liver disease, but also to extra-hepatic manifestations. Evidence Acquisitions: Directory of Open Access Journals (DOAJ), Google Scholar, Pubmed (NLM), LISTA (EBSCO) and Web of Science have been searched. Results: Herein, we provide an overview of renal diseases related to HCV and their therapies, as well as the treatment options available for HCV (+)/RNA (+) dialysis patients. We will not mention, however, HCV infection-related complications in the post-kidney transplantation setting. Conclusions: Extra-hepatic manifestations of HCV infection include mixed cryoglobulinemia, lymphoproliferative disorders, and renal disease. HCV infection has been reported in association with distinct histological patterns of glomerulonephritis in native kidneys.